Death, dying, and organ transplantation reconstructing medical ethics at the end of life - Miller, Franklin G.; Truog, Robert (Oxford : Oxford University Press, 2012)
Miller and Truog challenge fundamental doctrines of established medical ethics. They argue systematically that physicians legitimately cause the death of patients in the routine practices of withdrawing life support and vital organ donation.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Euthanasia -- Moral and ethical aspects; Procurement of organs, tissues, etc. -- Moral and ethical aspects